2016
DOI: 10.3389/fnins.2016.00222
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Alcohol Exposure: Burden of Epigenetic Reprogramming, Synaptic Remodeling, and Adult Psychopathology

Abstract: Adolescence represents a crucial phase of synaptic maturation characterized by molecular changes in the developing brain that shape normal behavioral patterns. Epigenetic mechanisms play an important role in these neuromaturation processes. Perturbations of normal epigenetic programming during adolescence by ethanol can disrupt these molecular events, leading to synaptic remodeling and abnormal adult behaviors. Repeated exposure to binge levels of alcohol increases the risk for alcohol use disorder (AUD) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 175 publications
(299 reference statements)
2
73
0
Order By: Relevance
“…It has long been appreciated that exposure to alcohol in utero leads to fetal alcohol spectrum disorders (FASD), but more recent research has concluded that exposure to alcohol during adolescence also causes long-lasting alterations to brain and behavior (Coriate et al, 2013; Kyzar et al, 2016a). Both FASD and adolescent alcohol exposure cause changes in the expression of epigenetic enzymes and chromatin conformation.…”
Section: Developmental Alcohol Exposure Causes Long-lasting Alteramentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been appreciated that exposure to alcohol in utero leads to fetal alcohol spectrum disorders (FASD), but more recent research has concluded that exposure to alcohol during adolescence also causes long-lasting alterations to brain and behavior (Coriate et al, 2013; Kyzar et al, 2016a). Both FASD and adolescent alcohol exposure cause changes in the expression of epigenetic enzymes and chromatin conformation.…”
Section: Developmental Alcohol Exposure Causes Long-lasting Alteramentioning
confidence: 99%
“…Adolescence is a critical period for brain development (Keshavan et al, 2014; Kyzar et al, 2016a; Crews et al, 2016). While most organs do not undergo noteworthy changes during the lifespan with regards to structure and function, the brain goes through important changes during early life and adolescence.…”
Section: Developmental Alcohol Exposure Causes Long-lasting Alteramentioning
confidence: 99%
See 1 more Smart Citation
“…During adolescence, epigenetic modifications play an important role in neurodevelopment, and interfering with these mechanisms is a risk factor that can result in developing neuropsychiatric disorders in adult life (Kyzar et al, 2016a). As observed in adult rats, acute alcohol treatment induced anxiolytic effects and the inhibition of HDAC activity in the amygdala of adolescent rats but required higher dose of ethanol as compared with adult rats (Sakharkar et al, 2012, 2014b).…”
Section: Epigenetic Mechanisms Of Alcohol Addictionmentioning
confidence: 99%
“…An acute ethanol challenge in adulthood can attenuate the anxiety-like behavior, the decrease in Lsd1+8a (a neuron-specific splice variant of LSD1), and reverse the increase of dimethylated H3K9 levels of the BDNF exon IV gene promoter in the amygdala induced by AIE (Kyzar et al, 2016b). Together with adolescent studies on histone acetylation, all these data suggest that alcohol exposure during early life or in adulthood can cause epigenetic alterations leading to changes in gene expression that, in turn, can regulate alcohol-related behaviors (Kyzar et al, 2016a). …”
Section: Epigenetic Mechanisms Of Alcohol Addictionmentioning
confidence: 99%